Secondary recycled polyvinylidene–limestone composite in 4D printing applications for heritage structures: Rheological, thermal, mechanical, spectroscopic, and morphological analysis. (April 2023) - Kumar, Vinay; Singh, Rupinder; Ahuja, Inderpreet Singh
Polymer 3D printing has motivated researchers toward the use of this technology for the maintenance and repair of heritage structures. This results in the exploration of different thermoplastic composites as smart materials having properties like programmable features (one-way, two-way), sensing, etc. Also, the excessive use of thermoplastics in various fields has resulted in plastic solid waste management issues. Several studies have been reported on plastic solid waste management with 3D printing. But hitherto little has been reported on the use of heritage site debris as reinforcement in the thermoplastic matrix for addressing issues of plastic solid waste management as well as for inducing controlled 4D capabilities; for better maintenance and repair of the heritage site with shorter maintenance and repair time. The present study is focused on secondary (2˚) recycling of polyvinylidene fluoride thermoplastic material by reinforcing limestone (CaCO3 of 220 mesh size as per American Foundry Society (AFS)) collected as debris from heritage site for 3D printing applications followed by an analysis of its possible 4D capabilities. Different compositions/proportions of polyvinylidene fluoride–limestone were explored for acceptable rheological (melt flow index and viscosity), thermal (based on differential scanning calorimetry), mechanical (based on universal testing machine), and spectroscopic properties (based on attenuated total reflection-Fourier transformed infrared and photoluminescence). Piezoelectric property analysis of 3D printable composition/proportion and shape-memory effect of each composition/proportion was performed to investigate the 4D characteristics of the proposed composite. The results of the study suggest that polyvinylidene fluoride–6% limestone is a better composition/ proportion with acceptable rheological, thermal, and mechanical properties (melt flow index 2.429 g/10 min, viscosity 12742.9 Pa-s, thermal heat capacity 31.66 Jg −1, and Young's modulus 286.56 MPa) for selected heritage structures. For 4D capabilities, piezoelectric coefficient (D33 21.79 pC/N) and shape recovery (44.31%) have been ascertained for the best composition/ proportion selected. Further morphological analysis has been reported to support the test results.